The Construction of Happiness among Rural Javanese Muslims - Yusuf, Moh. Asror; Robingatun, Robingatun; Sufirmansyah, Sufirmansyah; Widiyanto, Asfa (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2023)
Happiness is not a fixed entity but rather constructed by the individuals in their interaction with society. Happiness has been explored by religion, philosophy, and various academic disciplines, however, these concepts are constructed by the individuals following their respective contexts. Individuals’ understanding of happiness varies due to their unique circumstances. Therefore, it becomes important to study the concept of happiness that exists in society. This study is a qualitative field study. The respondents consisted of twelve individuals who are graduates of Islamic schools (madrasah) or Islamic boarding schools (pesantren) who work as teachers, traders, or farmers in Kediri Regency, East Java, Indonesia. Data collection methods which have been used in this study are documentation and in-depth interviews. The findings of the study show that respondents generally perceive happiness as a state of peaceful and contented mind due to the fulfilment of physical and spiritual needs accompanied by gratitude to God. In line with their views, their orientation towards happiness is generally religious or spiritual. For them, genuine happiness can be achieved when they can perform religious rituals and become closer to God. To attain genuine happiness, their religious or spiritual needs and desires must be fulfilled. However, they also do not have the same orientation towards happiness. The religious doctrines of happiness acquired from the madrasah or the pesantren seem to be maintained, although there are slight differences among the respondents. This indicates that their understanding of happiness is a construct based on the doctrines they have learned and their individual experiences over time.